The cognitive complexity of the leaders and their impact on the organizational flexibility of field research at the company's headquarters for the distribution of petroleum products - سعيد, هديل كاظم; عبد الستار, حلا صاحب (Journal of Economics and Administrative Sciences, 2019)
The present research aims to test the effect of cognitive complexity as an independent variable in organizational agility as a responsive variable among the leaders working at the headquarters of the Iraqi Petroleum Products Distribution Company. To conclude a number of recommendations that contribute in the organizational agility in the company, and due to the importance of this research in public organizations and its notable role in community organizations. The research was carried out on a random sample of 101 individuals out of a total of 308, which represents the high leaders in the company (general managers, head of departments, and division officials). A questionnaire was used as information and data collecting tool, with also the use of statistical programs for testing the hypothesis and to get results (SPSS, AMOS, EXCEL) as well as the utilizing of descriptive statistical methods (Percentages, arithmetic Mean, Standard Deviation, Coefficient of Variation, Simple Linear Regression, Determination Coefficient (2R), Path Analysis, Relative Importance, and Pearson’s Correlation Coefficient). The research reached a number of conclusions, the most important of which is the high level of the cognitive complexity variable within the company being investigated. There was weakness and decline in organizational agility. It was found that individual differences in understanding, understanding and manipulating difficult concepts, which have a significant role in influencing organizational agility, sensing opportunities and changes, The ability required at the organizational level to deal with them intelligently and respond effectively to them, and concluded the research with a set of recommendations for the company to contribute to the development of performance and the achievement of organizational goals.